1979
DOI: 10.1111/j.1471-0528.1979.tb10824.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Fetal Growth

Abstract: Consecutive ultrasonic measurements of the fetal head area, thorax area, abdomen area, head/thorax (H/T) area ratio and head/abdomen (H/A) area ratio were obtained from 100 patients with a normal pregnancy and from 186 patients with suspected intrauterine fetal growth retardation. Of all the measurements used, H/A area ratio was found to be most accurate in identifying intrauterine fetal growth retardation predicting 82.9 per cent at 33 weeks and 85.7 per cent at 36 to 38 weeks of gestation. This technique was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Linear growth of HA until about 36 weeks has been reported in humans with slowed growth thereafter. 33 Since BPD growth rate slows near term in the rhesus monkey, one would expect a mans.7, 20-22,27,31.32 JOURNAL OF CLINICAL ULTRASOUND similar change in the HA growth rate. Data analysis in this investigation, however, did not indicate this to be true.…”
Section: Discussionmentioning
confidence: 98%
“…Linear growth of HA until about 36 weeks has been reported in humans with slowed growth thereafter. 33 Since BPD growth rate slows near term in the rhesus monkey, one would expect a mans.7, 20-22,27,31.32 JOURNAL OF CLINICAL ULTRASOUND similar change in the HA growth rate. Data analysis in this investigation, however, did not indicate this to be true.…”
Section: Discussionmentioning
confidence: 98%
“…In some investigations the ratio fetal head/abdomen has been used to detect intra-uterine growth retardation (22,23,24,25,26,27). In some of these studies the prevalence of intra-uterine growth retardation has been high (23, 28,27) or not described (24,26). Comparative studies have shown abdominal measurements alone to be more useful than the ratio fetal head/abdomen, which is not surprising since symmetric growth retardation occurs in more than 80% of retarded growth in some studies (21).…”
Section: Discussionmentioning
confidence: 99%
“…A placental size below the 10th centile was seen with birthweights up to the 84th centile. Varma et al (1979) studied the predictive efficacy of AA measurements in 186 high-risk pregnancies where the prevalence of birthweight <loth centile was 1970. The sensitivity at 33 weeks gestation was 80% and very similar at 10 days before delivery.…”
Section: Discussionmentioning
confidence: 99%